Islamic traditions and Muslim youth in Norway - Jacobsen, Christine M., 1971- (Muslim Minorities, 2011)
A major question regarding Islam in Europe concerns the religiosity of "Muslim youth" - a category currently epitomizing both the fears and hopes of multicultural Europe. How are Islamic traditions engaged and reworked by young people, born and educated in European societies, and which modes of religiosity will they shape in the future? Providing an in-depth ethnographic account from Norway, this book engages comparative research on Islam and young Muslims from across Europe, focusing on Islamic revitalization, Muslim identity politics, changing configurations of religious authority, and the formation of gendered religious subjectivities. The author discusses anthropological and other social science theorizing in order to examine religious continuities and discontinuities in a context of international migration, globalization, and secular modernity.